Dual solutions for general three-dimensional MHD boundary layer stagnation-point flow of hybrid nanofluid and heat transfer - Zainal, Nurul Amira (Emerald Group Holdings Ltd., 2023)
Purpose – The evaluation of high thermal efficiency has actively highlighted the unique behaviour of hybrid nanofluid. Thus, the purpose of this paper is to emphasize the hybrid nanofluid’s stagnation point in three-dimensional flow with magnetic field. Design/methodology/approach – The defined ordinary differential equations systems are addressed using the bvp4c solver. Findings – The results indicate that using dual solutions is possible as long as the physical parameters remain within their specified ranges. Hybrid nanofluid flow has been recognised for its superior heat transfer capabilities in comparison to both viscous flow and nanofluid flow. Furthermore, it has been demonstrated in the current study that augmenting the volume concentration of nanoparticles leads to a corresponding enhancement in the rate of heat transfer. When the velocity gradients ratio is augmented, there is a corresponding reduction in the thermal performance. The separation value grows as the magnetic parameter rises, which signifies the expansion of the boundary layer. Originality/value – The originality of the paper highlights the general mathematical hybrid model of the three-dimensional problem with the magnetohydrodynamics (MHD) effect in the stagnation point flow.